Manifestations of Violence in the Arabic poetry of Enthusiasm: A case Study of Abu Ubeidah’s “The Days of Arabs” - chouiyat, abdelazzize (Milev Journal of Research and Studies, 2016)
Verbal violence was linked to physical violence in the old Arab life, and it was concomitant with it in their Bedouin life. The more Arabs were closer to the Bedouin life, the more they were violent. Physical violence reflects verbal violence in the same way a mirror reflects one’s face. That is why the pre-Islamic Arab environment, which is characterized by nomadism, was the arena of both physical and verbal violence. We can see this in Abu Ubeidah’s « The Book of the Days of Arabs », where he talks about the Arab wars in the pre-Islamic literature- poetry and prosethat accompanied and described them. He uses verbal violence which suits the tales of actual violence, including the fierce wars that shaped the Pre-Islamic Arab life.